Design and performance of an ecosystem‐scale forest soil warming experiment with infrared heater arrays. Issue 9 (11th July 2022) - Duan, Yihang; Liu, Dongwei; Huang, Kai; Shou, Wenkai; Zhu, Feifei; Liu, Yuqi; Yu, Haoming; Gundersen, Per; Kang, Ronghua; Wang, Ang; Han, Shijie; Wang, Zhiming; et al.
Abstract: How forest ecosystems respond to climate warming will determine forest trajectories over the next 100 years. However, the potential effects of elevated temperature on forests remain unclear, primarily because of the absence of long‐term and large‐size field warming experiments in forests, especially in Asia. Here, we present the design and performance of an ecosystem‐scale warming experiment using infrared (IR) heater arrays in a 60‐year‐old temperate mixed forest at Qingyuan Forest CERN in northeastern China. In paired 108 m 2 plots ( n  = 3), the surface soils were constantly elevated 2°C above control plots with a feedback control system over 4 years (2018–2021). Subsoils down to 60 cm depth were warmed 1.2–2°C. Soil warming did not significantly affect soil moisture either in surface soils or in subsoils. Turn‐off time due to weather extremes (heavy rains, snow) and power outages only accounted for 2.5% of the total warming period. In conclusion, we provide a proof‐of‐principle setup that allows long‐term analysis of forest response to warming temperatures in large‐size field plots. Importantly, our warming experiment demonstrated the feasibility of IR heater arrays for soil warming in tall‐statured forest ecosystems.